Repetitive Motion: Is A Risk Factor For Musculoskeletal Disorders Among Warehouse Workers? - Nima Eka Nur Rahmania; Ellyza Setya Maryiantari; Achmat Kuncoro; Riza Irianingtyas; Ratih Damayanti (STIKES Intan Martapura, 2026)
Introduction: Musculoskeletal Disorders (MSDs) are frequently found among warehouse workers due to manual handling activities and physical workloads during work processes. Objective: This study aimed to analyze the relationship between repetitive motion, physical workload, Body Mass Index (BMI), and MSDs among warehouse workers in Sidoarjo. Methods: An observational analytic study with a cross-sectional design was conducted on 40 animal feed warehouse workers using a total sampling technique. Repetitive motion were assessed using the Threshold Limit Value method from the American Conference of Governmental Industrial Hygienists (ACGIH), physical workload was measured using the Cardiovascular Load method, and musculoskeletal complaints were measured using the Nordic Body Map questionnaire. Data analysis was performed using the Chi-square or Fisher’s Exact test, Spearman correlation, and binary logistic regression. Results: The results showed that repetitive motion (p=0.01) and physical workload (p=0.04) were significantly associated with MSDs. Repetitive motion were the most dominant factor associated with MSDs (OR=2.8; 95% CI=1.21-6.42; p=0.02). BMI showed a borderline association with MSDs (p=0.05), whereas age, tenure, and exercise habits were not significantly associated. Conclusion: Repetitive motion and physical workload were significantly associated with MSDs.